Effects of Ocean Acidification on Resident and Active Microbial Communities of Stylophora pistillata - Barreto, Marcelle Muniz; Ziegler, Maren; Venn, Alexander; Tambutté, Eric; Zoccola, Didier; Tambutté, Sylvie; Allemand, Denis; Antony, Chakkiath Paul; Voolstra, Christian R.; Aranda, Manuel (Frontiers in Microbiology, 2021)
Ocean warming and ocean acidification (OA) are direct consequences of climate change and affect coral reefs worldwide. While the effect of ocean warming manifests itself in increased frequency and severity of coral bleaching, the effects of ocean acidification on corals are less clear. In particular, long-term effects of OA on the bacterial communities associated with corals are largely unknown. In this study, we investigated the effects of ocean acidification on the resident and active microbiome of long-term aquaria-maintained Stylophora pistillata colonies by assessing 16S rRNA gene diversity on the DNA (resident community) and RNA level (active community). Coral colony fragments of S. pistillata were kept in aquaria for 2 years at 4 different pCO2 levels ranging from current pH conditions to increased acidification scenarios (i.e., pH 7.2, 7.4, 7.8, and 8). We identified 154 bacterial families encompassing 2,047 taxa (OTUs) in the resident and 89 bacterial families including 1,659 OTUs in the active communities. Resident communities were dominated by members of Alteromonadaceae, Flavobacteriaceae, and Colwelliaceae, while active communities were dominated by families Cyclobacteriacea and Amoebophilaceae. Besides the overall differences between resident and active community composition, significant differences were seen between the control (pH 8) and the two lower pH treatments (7.2 & 7.4) in the active community, but only between pH 8 and 7.2 in the resident community. Our analyses revealed profound differences between the resident and active microbial communities, and we found that OA exerted stronger effects on the active community. Further, our results suggest that rDNA- and rRNA-based sequencing should be considered complementary tools to investigate the effects of environmental change on microbial assemblage structure and activity.